2005
DOI: 10.1182/blood-2004-07-2507
|View full text |Cite
|
Sign up to set email alerts
|

Generation of migratory antigen-specific plasma blasts and mobilization of resident plasma cells in a secondary immune response

Abstract: Maintenance of protective humoral immunity depends on the generation and survival of antibody-secreting cells. The bone marrow provides niches for long-term survival of plasma cells generated in the course of systemic immune responses in secondary lymphoid organs. Here, we have analyzed migratory human plasma blasts and plasma cells after secondary vaccination with tetanus toxin. On days 6 and 7 after immunization, CD19 ؉ / CD27 high /intracellular immunoglobulin G high (IgG high )/HLA-DR high /CD38 high /CD20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
438
2
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 393 publications
(488 citation statements)
references
References 48 publications
42
438
2
6
Order By: Relevance
“…Interestingly, total numbers of T CM did not significantly differ between PB and BM, which suggests that recently activated T CM preferentially migrate or expand in BM. In this context a study is of interest showing that secondary vaccination resulted in the mobilization of resident nonvaccine-specific plasma cells indicating competition for BM niches [25]. It would be of interest to study whether similar phenomena could be observed for CMV-specific T cells.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, total numbers of T CM did not significantly differ between PB and BM, which suggests that recently activated T CM preferentially migrate or expand in BM. In this context a study is of interest showing that secondary vaccination resulted in the mobilization of resident nonvaccine-specific plasma cells indicating competition for BM niches [25]. It would be of interest to study whether similar phenomena could be observed for CMV-specific T cells.…”
Section: Discussionmentioning
confidence: 95%
“…In this case, PRDM1/Blimp-1 can mediate repression of CIITA at pIII to turn off the expression of MHC-II. However, a portion of plasma cells migrate to sites of inflammation (45)(46)(47). The expression of PRDM1/Blimp-1 in these plasma cells is likely to prevent the up-regulation of CIITA from pIV in environments of ongoing IFN-␥ production.…”
Section: Discussionmentioning
confidence: 99%
“…In humans (re)vaccinated against tetanus, a wave of newly generated plasmablasts is detectable between days 6 and 8 after vaccination in the blood. In transwell migration assays, these plasmablasts migrate toward CXCL12 gradients 46. Outside of this time window, only few plasmablasts and plasma cells are detectable in blood, and most if not all of them are obviously derived from mucosal immune responses 48.…”
Section: Conditional Survival Of Memory Plasma Cells—the Memory Nichementioning
confidence: 99%